(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background The Fabrication an optical sensing devices base on different polishing losses (0.37, 0.68& 1.28dBm) and integrated by Graphene Oxide (GO). The sides polished of single mode Fiber used to resemble D- shape Fiber with area (2mm2) by removing outer jacket and cladding to generate an evanescent field on polishing area that used as optical sensing region. The optical sensing devices integrated by coat D- shape fiber with few layers ( 22-layers) of Graphene Oxide (GO) with a thickness of 0.09µm. The Performance D-Shaped Fiber has been done experiment by two test. First test of D-Shaped Fiber without coat done by applied acetone on polished region that show increase in transmitted power. Second test of D-Shape Fiber coated thin layer of graphene oxide (GO) that show increase in transmitted power, thus open promising way to be applied in many applications such as biomedical sensor, humidity sensor, temperature sensor. Materials and Methods: D- shape Fiber with different polishing losses and integrated Graphene Oxide (GO) Results: testing of Acetone by applied on polishing area that shows an increase in transmitting power Thus, transmitting power increased immediately due to a change in the refractive index from dry air to Acetone, which caused decreasing in power leakage that covered the sensing region. Conclusion: The testing D-Shape Fiber that coated with GO shows enhancement, fast response, highly sensitivity and stable measurement (without fluctuation) to acetone camper to D-Shape Fiber only.